Antimicrobial susceptibilities of Bacteroides fragilis and Bacteroides thetaiotaomicron strains isolated from clinical specimens and human intestinal microbiota - ÜLGER, NURVER (ELSEVIER SCI LTD, 2004)
Species of Bacteroides fragilis group bacteria are the most prevalent pathogens and have the highest resistance rates to antimicrobial agents among anaerobic bacteria. Infections due to these micro-organisms often originate from patient's own intestinal microbiota. The objective of the study was to determine and compare the susceptibility profiles of clinical and intestinal B. fragilis and B. thetaiotaomicron strains against certain antimicrobials. Isolates were identified by conventional methods and API-20 A. Susceptibility tests were performed according to recommendations of NCCLS (M 11-A4) agar dilution methods. Beta-lactamase production was determined with nitrocefin discs. Forty-five clinical isolates (33 B. fragilis and 12 B. thetaiotaomicron) were from following sites: blood (n:8), intra-abdominal abscess (n:7), soft tissue (n:26), and miscellaneous foci of infection (n:4). Fifty B. fragilis and 60 B. thetaiotaomicron isolates from intestinal microbiota of individuals with no history of antimicrobial treatment within last 30 days were also examined. Beta-lactamase production was detected in 93% of clinical and 99% of intestinal isolates. The organisms including intestinal isolates were uniformly susceptible to metronidazole. The MIC90s of other antibiotics and resistance rates of all clinical isolates to those antibiotics were as follows: 256 mug/mL (93%) for ampicillin, 128 mug/mL (13%) for piperacillin, 64 mug/mL (11%) for cefoxitin, 1 mug/mL (2%) for amoxicillin-clavulanate, 0.5 mug/mL (2%) for imipenem, > 256 mug/mL (36%) for clindamycin, 8 mug/mL (2%) for chloramphenicol. Intestinal isolates demonstrated similar resistance rates and MIC90s. Metronidazole, imipenem, amoxicillin-clavulanate seem to be effective drugs against these bacteria in Turkey. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Bacteroides fragilis; Bacteroides thetaiotaomicron; antimicrobial susceptibility; ANTIBIOTIC SUSCEPTIBILITY; ANAEROBIC-BACTERIA; GROUP ORGANISMS; BETA-LACTAM; RESISTANCE; CLINDAMYCIN; METRONIDAZOLE; PATTERNS; AGENTS